A Factor V Genetic Component Differing From Factor V R506Q Contributes to the Activated Protein C Resistance Phenotype - Bernardi, F.; Faioni, E.M.; Castoldi, E.; Lunghi, B.; Castaman, G.; Sacchi, E.; Mannucci, P.M. (Blood, 1997)
Factor V gene polymorphisms were investigated to detect components that may contribute to the activated protein C (APC) resistance phenotype in patients with venous thromboembolism. A specific factor V gene haplotype (HR2) was defined by six polymorphisms and its frequency was found to be similar in normal subjects coming from Italy (0.08), India (0.1), and Somalia (0.08), indicating that it was originated by ancestral mutational events. The relationship between the distribution of normalized APC ratios obtained with the functional assay and haplotype frequency was analyzed in patients heterozygous for factor V R506Q (factor V Leiden). The HR2 haplotype was significantly more frequent in patients with ratios below the 15th percentile than in those with higher ratios or in normal controls. Moreover, the study of 10 patients with APC resistance in the absence of the factor V R506Q mutation showed a 50-fold higher frequency of HR2 homozygotes. The HR2 haplotype was associated with significantly lower APC ratios both in patients with venous thromboembolism and in age- and sex-matched controls. However, the two groups showed similar HR2 haplotype frequencies. Plasma mixing experiments showed that an artificially created double heterozygote for the factor V R506Q mutation and the HR2 haplotype had an APC ratio lower than that expected for a simple R506Q heterozygote. Time-course experiments evaluating the decay of factor V in plasma showed the normal stability of the molecule encoded by the factor V gene marked by the HR2 haplotype, which ruled out the presence of a pseudo-homozygous APC resistance mechanism. Our results provide new insights into the presence of factor V genetic components other than the factor V R506Q that are able to contribute to the APC resistance phenotype in patients with venous thromboembolism.